Scaling nutrition-sensitive rice-based food systems in Africa: Africarice’s contribution to the healthydiets4africa project- 2025 progress report - Ndindeng, S.A. (2025)
Under the HealthyDiets4Africa (HD4A) project—Combating Malnutrition in Africa Through Diversification of the Food System—the Africa Rice Center (AfricaRice) has delivered substantial, evidence-based contributions to the design, testing, and scaling of nutrition sensitive rice-based food systems across multiple African countries. Funded by the European Union under Horizon Europe, HD4A positions food system diversification as a central pathway to addressing malnutrition, diet-related non-communicable diseases, and food system resilience. During the reporting period, AfricaRice’s contributions progressed decisively from research and piloting toward Scaling for Impact, anchored in Living Labs, youth-led agribusiness development, improved processing and storage technologies, and policy-relevant nutrition evidence. AfricaRice’s work focused on strengthening the nutritional quality, safety, affordability, and market uptake of rice and diversified food products, while ensuring institutional embedding and scalability. Guided by CGIAR-aligned Scaling for Impact principles, AfricaRice demonstrated how nutrition-sensitive rice value chain upgrading—combined with diversified foods, youth employment, and institutional demand—can deliver measurable nutrition, economic, and social outcomes at scale. Major Scaling Achievements Led by AfricaRice Across Côte d’Ivoire, Nigeria, Cameroon, Kenya, Liberia, and Uganda, AfricaRice delivered the following key scaling results: • Generation of large-scale scientific evidence on the nutritional superiority of Oryza glaberrima, based on the analysis of 5,219 rice accessions, demonstrating significantly higher protein (mean 15.2%, up to 28.3%) and superior iron and zinc content compared with O. sativa. This evidence underpins nutrition-sensitive breeding, product development, and donor investment strategies. • Development of nutrition-sensitive rice products, including: o Iron–zinc fortified parboiled rice, o Low-glycaemic-index (low-GI) parboiled rice, o Fortified rice crackers enriched with indigenous African crops (moringa, baobab, hibiscus, soybean, tiger nut), achieving protein levels up to 20.2% and high mineral bioavailability. • Operationalization of Living Labs in Bouaké (Côte d’Ivoire), Abuja (Nigeria), Dschang (Cameroon), Liberia, Kenya (Nairobi and Makueni), and Uganda, serving as platforms for co-design, production, processing, consumer testing, and market uptake of healthy diets. • Youth skills development and employment creation, with: o Over 400 youth trained directly across AfricaRice-supported Living Labs, o Dozens of youth-led agribusinesses established, including 72 enterprises in Nigeria, and o Permanent jobs created through operational processing units (e.g. five permanent positions at the Bouaké Living Lab rice processing unit). • Large-scale production of healthy foods, including: o ≈697 tonnes of diversified healthy foods produced in Côte d’Ivoire, o 57,390 kg of healthy foods produced by youth enterprises in Nigeria, o 70,124 kg reported from Cameroon Living Labs. • Strengthening of nutrition-sensitive processing and post-harvest systems, through: o Deployment of GEM parboiling systems, o Solar–gas hybrid dryers (with 10 technicians trained from eight countries), o Hermetic storage systems shown to double seed viability and improve milling returns by ~2%. • Consumer acceptance and behavior-change evidence, including a large-scale study in Uganda involving 765 households, showing strong acceptance (mean score 4.18/5) of nutrient-dense black rice despite >93% prior unfamiliarity. • Policy and financing influence, notably AfricaRice’s catalytic contribution to mobilizing CAD 1 million in innovative financing from IDRC/CRDI for the AlimSco school feeding–local production model in Côte d’Ivoire, linking school canteens with local rice and vegetable value chains. Progress Toward Scaling and Sustainability AfricaRice’s HD4A contributions are firmly positioned within the expansion and institutionalization phase of Scaling for Impact. Innovations are no longer confined to research settings but are embedded within: • Youth-led enterprises and vocational hubs, • Operational rice processing units and Living Labs, • School feeding systems and institutional procurement, • National research and extension platforms, • Donor-financed follow-on initiatives (e.g. CRDI-funded AlimSco). By integrating nutrition science, processing innovation, youth entrepreneurship, and institutional demand, AfricaRice has demonstrated a replicable and scalable model for transforming rice-based food systems toward healthier, safer, and more inclusive diets in Africa.